A Reflection on Light as a Medium: Surveillance, the Sublime, and Poetics in Montreal’s Nocturnal Landscape - Bertin, Sylvain (Intermédialités / Intermediality)

(untitled) (Revue intermédialités, 2015)
This article questions light mediation forms in the city during the night. Lighting regulates the perception of the city and its activities. Through a discussion of the evolution of lighting mediation forms like control, sublime, and spectacle, this paper examines urban lighting strategies and the transformation of the city’s image influenced by the lit environment. Furthermore, the motivations and the limitations of lighting mediation are questioned. To illustrate these ideas, the article examines the case study of Montreal’s nocturnal landscape. Through the control of the perception of darkness, the sublimity of economic power, and the excitement caused by spectacular lighting, the night discloses new experiences of the city.